Unilateral Ovarian Absence with Ipsilateral Fallopian Tube Agenesis in Secondary Infertile Patient - Dr Renu Verma; Dr Mini; Dr Achala Batra (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Congenital agenesis of the unilateral adnexa is a condition that has rarely been described in the literature. The current study presents the case of a 34-year-old female who was admitted to the Department of Gynaecology at the Mata Gujari Hospital, hospital, new Delhi, India for secondary infertility. The patient was diagnosed with unilateral ovarian and unilateral fallopian tubal agenesis, without malformations of the uterus and urinary tract, during diagnostic laparoscopy. A literature review was conducted with the aim of determining the possible causes of these anomalies. However, the etiology of the adnexal anomaly remained unclear, although torsion or congenital defects were the most likely explanation. Therefore, the observations of the present study indicate that contralateral tubal pathologies may contribute to sterility.